Empowering educators: the transformative potential of generative AI in education - UiTM, Pejabat Timbalan Naib Canselor (Penyelidikan & Inovasi) (Office of the Deputy Vice-Chancellor (Research & Innovation), 2024)
RISE Magazine is published by Department of Research and Innovation with aims to highlight a research and innovation on multidisciplinary expert of fields in UiTM. It serves as a platform for researcher to showcase their high quality and impactful findings, activities and innovative solution through publication. Contribution of these ideas come from academicians, researchers, graduates and universities professionals who will enhance the visibility of research and stride to elevate Universiti Teknologi MARA to global standards. This is an effort to promote research as a culture that is accepted by all expertise.